The Subject in the Crowd: A Critical Discussion of Jodi Dean’s “Crowds and Party” - Jacob Johanssen (tripleC: Communication, Capitalism & Critique, 2016)
This article presents a critical discussion of Jodi Dean’s (2016) book “Crowds and Party”. I pay particular attention to her discussion of crowds that is influenced by psychoanalysis. Dean has put forward an important argument for the affectivity within crowds that may be transformed into a Communist Party that is characterised by a similar affective infrastructure. I suggest that Dean’s discussion of affect is slightly vague at times and may be supplemented with Sigmund Freud’s work on affect. In contrast to Dean, who stresses the collectivity and deindividuation of the crowd, I argue that the crowd needs to be thought of as a place where individuality and collectivity come together and remain in tension.